Antidepressant properties of mitragynine, an alkaloid isolated from mitragyna speciosa korth, in mice model of depression - Nasir, Farah Idayu (2013)
Major depressions are among the most prevalent disease of the central nervous system with a high morbidity and mortality. Available antidepressants that used as pharmacotherapy for depression produce a lot of adverse effects towards depressed patient. Therefore, safer treatments for treating mental illness like depression are still needed. On the other hand, drugs obtained from natural sources are perceived to have at least risk and low side- effects profiles, while having the ability to cure mental disorder. Mitragynine (MG) is the major alkaloid identified in Mitragyna speciosa Korth which has been used in traditional medicine. The antinociceptive action of MG is due to its role on opioid system to stimulate the release of endogenous noradrenaline and serotonin from nerve terminal. However, none has been reported on the mechanism action of MG via spectrum of antidepressant studies. Based on the principle that MG has a significant role in producing antinociceptive action, it might as well beneficial as antidepressant. Hence, the present investigation evaluated the antidepressant effect of MG in the mouse forced swim test (FST) and tail suspension test (TST) together with its effects on hypothalamic-pituitary-adrenal (HPA) axis by measuring the corticosterone concentration of mice exposed to FST and TST. An open-field test (OFT) was used to study any association of immobility in the FST and TST with psychomotor stimulant effect of MG. Male ICR mice were randomly assigned to six treatment groups (n=8): Group I (vehicle control group), Group II received reference drug 20 mg/kg, fluoxetine (selective serotonin reuptake inhibitor, SSRI), Group III received tricyclic antidepressant drug, amitriptyline hydrochloride 10 mg/kg and Group IV, V and VI received 5,10 and 30 mg/kg of MG. MG at doses of 10 mg/kg and 30 mg/kg significantly reduced the immobility time of mice in both FST and TST without any significant effect on locomotor (crossing) activity in OFT. Moreover, MG significantly reduced the released of corticosterone in mice exposed to FST and TST at dose of 10 mg/kg and 30 mg/kg.In order to investigate the involvement of MG on cannabinoid system, a group of animals were randomly assigned into four experimental groups (8 mice per group). The groups were consist of group I,that served as control treatment; group II was given MG (10 mg/kg i.p.); group III was given cannabinoid receptor (CB1) antagonist drug, AM 251 (0.5 mg/kg i.p.) and finally group IV was given pre-treatment of AM 251 (0.5 mg/kg i.p.) followed by treatment of MG (10 mg/kg i.p.). The results showed that pretreatment of mice with AM 251 produced significant reduction in immobility time as compared with treatment of MG alone and treatment of AM 251 alone. In terms of corticosterone level, pre- treatment of mice with AM 251 significantly increasedthe level of corticosterone concentrations as compared with treatment of MG alone and treatment of AM 251 alone after exposed to FST and TST. These data suggest antidepressant effect produced by MG is not likely through its action on cannabinoid receptor system.